Time Frame Affects Vantage Point in Episodic and Semantic Autobiographical Memory: Evidence from Response Latencies - Karylowski, Jerzy J.; Mrozinski, Blazej (Frontiers in Psychology, 2017)
Previous research suggests that, with the passage of time, representations of self in episodic memory become less dependent on their initial (internal) vantage point and shift toward an external perspective that is normally characteristic of how other people are represented. The present experiment examined this phenomenon in both episodic and semantic autobiographical memory using latency of self-judgments as a measure of accessibility of the internal versus the external perspective. Results confirmed that in the case of representations of the self retrieved from recent autobiographical memories, trait-judgments regarding unobservable self-aspects (internal perspective) were faster than trait judgments regarding observable self-aspects (external perspective). Yet, in the case of self-representations retrieved from memories of a more distant past, judgments regarding observable self-aspects were faster. Those results occurred for both self-representations retrieved from episodic memory and for representations retrieved from the semantic memory. In addition, regardless of the effect of time, greater accessibility of observable (versus unobservable) self-aspects was associated with the semantic rather than episodic autobiographical memory. Those results were modified by neither declared trait’s self-descriptiveness (yes versus no responses) nor by its desirability (highly desirable versus moderately desirable traits). Implications for compatibility between how self and others are represented and for the role of self in social perception are discussed.